2001
DOI: 10.1176/appi.ajp.158.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline Treatment of Generalized Social Phobia: A 20-Week, Double-Blind, Placebo-Controlled Study

Abstract: Sertraline is an effective treatment for patients with generalized social phobia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(103 citation statements)
references
References 27 publications
(18 reference statements)
9
87
3
Order By: Relevance
“…Relapse rates were significantly lower in the paroxetine group (Stein et al 2002b)(A). Á Sertraline has been shown to be effective in DBPC studies: (Blomhoff et al 2001;Katzelnick et al 1995;van Ameringen et al 2001). The efficacy has also been shown in the long term.…”
Section: Summary Of Recommendations For the Treatment Of Gadmentioning
confidence: 99%
See 1 more Smart Citation
“…Relapse rates were significantly lower in the paroxetine group (Stein et al 2002b)(A). Á Sertraline has been shown to be effective in DBPC studies: (Blomhoff et al 2001;Katzelnick et al 1995;van Ameringen et al 2001). The efficacy has also been shown in the long term.…”
Section: Summary Of Recommendations For the Treatment Of Gadmentioning
confidence: 99%
“…The efficacy has also been shown in the long term. In one 24-week DBPC study (Blomhoff et al 2001) and a 24-week relapse prevention study following a 20-week DBPC study (van Ameringen et al 2001), the efficacy of sertraline could be demonstrated (A). Á Citalopram was effective in one DBPC study (Furmark et al 2005)(B).…”
Section: Summary Of Recommendations For the Treatment Of Gadmentioning
confidence: 99%
“…However, a high percentage of SAD patients fail to respond to the available treatment options, or achieve only partial remission of symptoms, with antidepressants providing the best response rates Baldwin et al, 1999;Van Ameringen et al, 2001). Given the high prevalence and unsatisfactory treatment options for SAD, a better understanding of the etiology and underlying neurobiological mechanisms of social fear, particularly extinction of social fear, is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Van Amering et al 25 evaluated sertraline vs. placebo in 204 generalized SAD patients for a 20-week doubleblind study. The dosing was flexible up to a maximum of 2000mg/day.…”
Section: Serotonin-specific Reuptake Inhibitors (Ssris)mentioning
confidence: 99%